Poisonous Honey or Pure Manna: The Eucharist and the Word in the “Beehive” of Marnix of Saint Aldegonde - Beemon, F. E. (Church history, 1992)
With the publication of his Den Byencorf der H. Roomische Kercke (The Beehive of the Holy Roman Church) in 1569, the Netherlandic Calvinist Marnix of Saint Aldegonde launched a satirical attack onthe clergy, polity, and sacramental practice of Catholicism. Though the fame of the book and its author have been eclipsed, they were both well known during the sixteenth and seventeenth centuriesas shown by the frequency of publication. Marnix's task, in common with other sixteenth-century religious propagandists, was to communicate a theological message to a popular audience. The success of this effort depended on reaching across the separation between systematic theology and folk religiosity. The object was not original theology, nor even doctrinal subtleties, but the creativeuse of common terms to explain divergent schemes of basic dogma. Because the subject was more religious than theological, the separation between Latin and the vernacular cultures could be bridged by the use of metaphors common to both high and popular culture. In this, Marnix's work is distinguished by his use of the metaphors of beehive, honey, and manna to explain the differences between the Catholic Eucharist and the Calvinist Lord's Supper. The use of manna is not surprising as one would expect it to be a common image; however, the metaphors of hive and honey are less expected. While the former is clearly biblical in origin, the apiary metaphors are not. Thus, Marnix relies on the common sociocultural context of the beehive to instruct a popular Dutch audience in a fundamental difference between Calvinism and Catholicism. By identifying the Catholic host with polluted honey, Marnix defends the necessary presence of the Word for the Calvinist Lord's Supper, which he portrays as pure manna. Rather than feeding on the body of Christ, Marnix argues, the true Church feeds on the Word of God, which is present in the Calvinist wafer.